Կապանի լեռնահարստացման կոմբինատի գեղանուշի պոչամբարի շրջակայքում և զանգեզուրի պղնձամոլիբդենային կոմբինատի բացահանքի ու արծվանիկի պոչամբարի հարակից տարածքներում γ-ֆոնի և նմուշառումների ուսումնասիրություն - Առաքելյան, Ա. Ս.; Գևորգյան, Ա. Ա.; Ղազարյան, Մ. Գ.; Մարուխյան, Ո. Զ.; Սևոյան, Գ. Գ.; Փյուսկյուլյան Կ. Ի. («Պոլիտեխնիկ» տպ.)
Представлены результаты исследования гамма-фона в окрестностях Геганушского и Арцваникского хвостохранилищ, эксплуатируемых Капанским горно-обогатительным и Зангезурским медно-молибденовым комбинатами, и карьера Зангезурского медно-молибденового комбината. Приведены также результаты гамма-спектрометрических анализов образцов пород, взятых из карьера Зангезурского медно-молибденового комбината. Исследование и измерение γ-фона производились с использованием системы SPARCS-M1. Радиационно-экологическое исследование с оценкой гамма-фона вышеназванных территорий было проведено согласно договорам, подписанным Национальным политехническим университетом Армении и ООО “Биогеотех”. The results of the study of the gamma background in the vicinity of the Geghanush and Artsvanik tailings operated by the Kapan Mining and Processing and Zangezur Copper- Molybdenum Combines, and the open pit of the Zangezur Copper-Molybdenum Combine are introduced. The results of gamma-spectrometric analyses of rock samples taken from the open pit of the Zangezur Copper-Molybdenum Combine are presented. The measurement of the γ-background was carried out using the SPARCS-M1 system. The radiation-ecological study with the assessment of the gamma background of the above-named territories was carried out in accordance with the agreements signed by National Polytechnic University of Armenia and “Biogeotech” LLC.
Keywords: Էներգետիկա